A busca do processo penal constitucional : audiência de custódia e o contraditório na investigação preliminar - Castro, Fabiana Oliveira Bastos de (2017)
The purpose of this dissertation is to identify whether a custodial audience in civilizing the arrest warrant, reverencing the principles of the adversary and ample defense from the beginning of the criminal prosecution, will allow the emergence of a new policy on preliminary investigation, now oriented towards the Fundamental guarantees, especially of the contradictory in the investigative phase. In this way, it is intended to increase knowledge about the custody hearing, aiming to identify its origin, define its characteristics, the way it was implanted in the Brazilian legal system, and also evaluate the purpose of the presentation of the prisoner immediately to the Judge and impartiality Of the trial judge attending the hearing. In addition, it is sought to ascertain the characteristics and assumptions of the preliminary investigation, it also inquires about the possibility of applying the contradictory and its importance in the Brazilian preliminary investigation. In the end, we will discuss the Kafkian criminal proceedings, the compatibility of the contradictory in the preliminary investigation in light of the Brazilian procedural system, as well as if the custodial audience has the possibility to modify inquisitorial paradigms still present in our criminal policy. To do so, the existing literature will be reviewed, exploring studies on Criminal Procedural Law and Constitutional Law, especially by consulting books, dissertations and monographs published by Brazilian and foreign authors, aiming to broaden the knowledge about the topic discussed.